2015
DOI: 10.1177/1403494815615763
|View full text |Cite
|
Sign up to set email alerts
|

Adverse lifestyle and health-related quality of life: gender differences in patients with and without chronic conditions

Abstract: Adverse lifestyle had the most expressed association with HRQoL in women with CCs. Light alcohol consumption had a positive association, but harmful use of alcohol had an inverse association with HRQoL irrespective of patients' gender or health status.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 23 publications
1
8
1
1
Order By: Relevance
“…In a study conducted in Sweden [16] to examine gender diff erences in the interpreta on of self-rated health, chronic disease explained twice as much of the variance of regression analyses in self-rated health for women versus men. Furthermore, they found that overall general physical ac vity was more important for men, while for women, having a chronic disease was associated with lower self-reported health [15]. S ll, unlike the previous study, our results demonstrated that the gender diff erence in values of HRQoL cannot be explained by systemic infl amma on, as there was no signifi cant diff erence in hsCRP for both genders [17].…”
Section: Health-related Quality Of Life and Physical Func Oncontrasting
confidence: 56%
See 1 more Smart Citation
“…In a study conducted in Sweden [16] to examine gender diff erences in the interpreta on of self-rated health, chronic disease explained twice as much of the variance of regression analyses in self-rated health for women versus men. Furthermore, they found that overall general physical ac vity was more important for men, while for women, having a chronic disease was associated with lower self-reported health [15]. S ll, unlike the previous study, our results demonstrated that the gender diff erence in values of HRQoL cannot be explained by systemic infl amma on, as there was no signifi cant diff erence in hsCRP for both genders [17].…”
Section: Health-related Quality Of Life and Physical Func Oncontrasting
confidence: 56%
“…The reasons for such a diff erence between genders might be the age gap and the considerably low number of men with self-reported chronic diseases compared with women. An increase in the number of chronic diseases has been reported to have a nega ve impact on HRQoL [15]. In a study conducted in Sweden [16] to examine gender diff erences in the interpreta on of self-rated health, chronic disease explained twice as much of the variance of regression analyses in self-rated health for women versus men.…”
Section: Health-related Quality Of Life and Physical Func Onmentioning
confidence: 99%
“…However, this association presented only among the younger patients. The results of a previous study suggested that older age combined with hazardous or harmful drinking had a negative association with PCS [14]. Thus, it is possible that among the middle-aged and older patients, the lower PCS is a reflection of the consequences of prolonged hazardous or harmful drinking, and for that reason, the positive effect of decreased AC on the PCS is less expressed line and follow-up AUDIT scores and HRQoL PCS or MCS based on gender.…”
Section: Key Results and Interpretationmentioning
confidence: 95%
“…Harmful AC significantly contributes to the burden of chronic diseases and conditions [10] and is implicated in reduced health-related quality of life (HRQoL) [11][12][13], irrespective of a person's gender or health status [14]. Thus, reduced AC is expected to lead to improved health; however, the evidence for health-related outcomes with reference to behavioral counselling interventions remains insufficient [15].…”
Section: Introductionmentioning
confidence: 99%
“…Todavia, o impacto dessas doenças na qualidade de vida diferencia-se de acordo com aspectos socioeconômicos e culturais (1,8) . Vários estudos atribuem uma menor qualidade de vida na população feminina, à alta proporção de angústia, depressão, estresse, ansiedade, distúrbios no sono e diferenças biológicas que são encontrados em mulheres, principalmente, em idade reprodutiva (1,(9)(10) . Com relação ao estado civil, não foi verificado se há interferência na QV das mulheres, ao contrário de outros estudos (11)(12) , em que pacientes que viviam com parceiro tinham uma QV melhor, quando comparadas às que viviam sozinhas.…”
Section: Discussionunclassified